Pesantren Tradition-based Nationalism Education Model on Religious Moderation Perspectives in Kediri, East Java - Edi Nurhidin (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
Shaping nationalist attitudes and moderate religious understanding in pesantren (Islamic boarding schools) is based on studying from the Kitab Kuning (classical Islamic textbooks written in Arabic). This paper explores nationalism values in the salafiyah pesantren traditions and brings them into the concept of religious moderation. This study employed a qualitative research method with a case study approach. Pesantren head and families, old alumni, and asatiz (pesantren teachers) of the salafiyah pesantren volunteered to participate. Secondary data were garnered through documents in the form of the kiai’s handwriting and old photographs in terms of the pesantren tradition practices. The study findings indicate two distinctive pesantren traditions, i.e., the qasidah (a traditional Islamic music performance) tradition and the Indonesian Independence Day ceremony. The two traditions contain nationalist values and meanings taught to santri (pesantren students) and have been going on for over half a century. This proves that nationalism education in salafiyah pesantren has a distinctive model. Therefore, nationalism education practices in pesantren have two essential contributions to national unity and integrity: strengthening santri nationalism and moderate religious understanding and practice.